Further Evidence on Using a Deadline to Stimulate Responses to a Mail Survey; Readership and Coverage of Science and Technology in Newspapers; The Uses and Gratifications Approach to Mass Communications Research - Larry Meiner; Lloyd R. Bostian (Journal of Applied Communications, 1979)
Reviews of Further Evidence on Using a Deadline to Stimulate Responses to a Mail Survey by Robert Roberts, Owen McCrory and Ronald Forthofer; "Readership and Coverage of Science and Technology in Newspapers," by Clyde Z. Nunn; "The Uses and Gratifications Approach to Mass Communications research," edited by David L. Swanson.